2019
DOI: 10.1002/gj.3527
|View full text |Cite
|
Sign up to set email alerts
|

Charging history and fluid evolution for the Carboniferous volcanic reservoirs in the western Chepaizi Uplift of Junggar Basin as determined by fluid inclusions and basin modelling

Abstract: Fluid inclusions are rich in the Carboniferous volcanic reservoirs in the western Chepaizi Uplift, occurring in liquid, gaseous, and gas–liquid phases. In this study, the fluid inclusions were investigated in terms of petrographic, optical, and microthermometric characteristics, coupled with pressure–volume–temperature–composition (PVTX) simulations. Two periods of hydrothermal activities in the Carboniferous volcanic reservoirs were suggested by the bimodal distributions of Th (homogenization temperatures) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
(71 reference statements)
1
11
0
Order By: Relevance
“…Many literature studies show that the Mesozoic reservoir has experienced at least three fillings, once in the Jurassic (family A1) and twice in the Cretaceous (families A2 and A3). The homogenization temperatures ( Th ) were 52.9–73.4 °C (with high salinity), 71.7–80.9 °C (with high salinity), and 120.0–130.0 °C (with low salinity), respectively. However, it seems that even the greatest paleotemperature and formation pressure that the Mesozoic interval experienced were lower than the above-mentioned fluid traps and trapping pressures according to the investigated geological evolution of burial–thermal–pressure histories. , This abnormal phenomenon was similar to the cases in the Carboniferous and Neogene petroleum reservoirs in the eastern Chepaizi Uplift. ,, Thus, many literature studies reported that the paleofluid with high temperature and high pressure was involved in deep hydrothermal fluid activities and charged the study area so quickly that the paleofluid was trapped in calcite and quartz veins before the temperature decreased to the formation temperature. Referencing the petroleum generation history, ,,, the sealing process of the Hongche Fault Zone, ,, and the charging history of neighboring petroleum reservoirs in the Chepaizi and Chunfeng oilfields, ,, the charging timeframe can be tentatively identified. From the Late Triassic-Early Jurassic, previous reconstruction burial and thermal history showed that the Permian source interval reached the threshold of hydrocarbon generation and entered into the peak oil window in the Middle and Late Jurassic. ,,, From the Late Jurassic-Late Cretaceous, the Hongche Fault Zone experienced strike-slip, dipping, and tension movements, ,, thus possibly formed a petroleum accumulation of early period ( Th : 52.9–73.4 and 71.7–80.9 °C) in the Mesozoic interval, which was subjected to biodegradation or loss because of its shallow depth and poor preservation.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Many literature studies show that the Mesozoic reservoir has experienced at least three fillings, once in the Jurassic (family A1) and twice in the Cretaceous (families A2 and A3). The homogenization temperatures ( Th ) were 52.9–73.4 °C (with high salinity), 71.7–80.9 °C (with high salinity), and 120.0–130.0 °C (with low salinity), respectively. However, it seems that even the greatest paleotemperature and formation pressure that the Mesozoic interval experienced were lower than the above-mentioned fluid traps and trapping pressures according to the investigated geological evolution of burial–thermal–pressure histories. , This abnormal phenomenon was similar to the cases in the Carboniferous and Neogene petroleum reservoirs in the eastern Chepaizi Uplift. ,, Thus, many literature studies reported that the paleofluid with high temperature and high pressure was involved in deep hydrothermal fluid activities and charged the study area so quickly that the paleofluid was trapped in calcite and quartz veins before the temperature decreased to the formation temperature. Referencing the petroleum generation history, ,,, the sealing process of the Hongche Fault Zone, ,, and the charging history of neighboring petroleum reservoirs in the Chepaizi and Chunfeng oilfields, ,, the charging timeframe can be tentatively identified. From the Late Triassic-Early Jurassic, previous reconstruction burial and thermal history showed that the Permian source interval reached the threshold of hydrocarbon generation and entered into the peak oil window in the Middle and Late Jurassic. ,,, From the Late Jurassic-Late Cretaceous, the Hongche Fault Zone experienced strike-slip, dipping, and tension movements, ,, thus possibly formed a petroleum accumulation of early period ( Th : 52.9–73.4 and 71.7–80.9 °C) in the Mesozoic interval, which was subjected to biodegradation or loss because of its shallow depth and poor preservation.…”
Section: Resultsmentioning
confidence: 85%
“…1,24,47 Thus, many literature studies reported that the paleofluid with high temperature and high pressure was involved in deep hydrothermal fluid activities and charged the study area so quickly that the paleofluid was trapped in calcite and quartz veins before the temperature decreased to the formation temperature. 43−47 Referencing the petroleum generation history, 43,44,46,47 the sealing process of the Hongche Fault Zone, 1,22,48 and the charging history of neighboring petroleum reservoirs in the Chepaizi and Chunfeng oilfields, 3,44,45 the charging timeframe can be tentatively identified. From the Late Triassic-Early Jurassic, previous reconstruction burial and thermal history showed that the Permian source interval reached the threshold of hydrocarbon generation and entered into the peak oil window in the Middle and Late Jurassic.…”
Section: Effect and Response Of Selectedmentioning
confidence: 99%
“…Combing the ratios of C 27 diasterane 20S/20R (C 27 DS 20S/20R), C 27 diasterane/C 27 regular sterane (C 27 DS/C 27 RS), C 26 /C 28 triaromatic steroid (20S) (C 26 /C 28 TAS(20S)), and C 27 /C 28 TAS(20R) with the stable carbon isotope distribution, previous studies concluded that the Carboniferous oils in the eastern Chepaizi Uplift were mainly derived from the mudstone of the Middle Permian Wuerhe Formation (P 2 w) in the Changji Sag, whereas the ones in the western Chepaizi Uplift were essentially originated from the Jurassic mudstone in the Sikeshu Sag (Zhang et al 2012;Xu et al 2018;Mao et al 2020). Although two oil charging episodes were defined in the Carboniferous reservoirs based on the oil geochemistry, fluid inclusions and basin modeling (Chang et al 2019;Shi et al 2020), the later charge actually was the remigration of early reservoired oils due to the tectonic adjustment (Cao et al 2010;Song et al 2016;Chang et al 2019). Although the Carboniferous oils all exhibited the characteristics of lacustrine source facies, source-diagnostic and redox potential of depositional environment-related molecular biomarkers showed marked distinction between the eastern and western parts (Xu et al 2018), implying at least two oil groups.…”
Section: Oil Bulk Compositions and Oil Familiesmentioning
confidence: 99%
“…Processes other than biodegradation, i.e., secondary oil charge, water washing, mixing of multiple maturity oil charges, and loss of light ends from heavy oils could produce variations in oil viscosity and API gravity (López 2014). The two episodes of oil charging, early biodegraded oils mixed with the later remigration of preexisting oils due to the structural adjustment, yet the same oil origin in the Chepaizi Uplift maybe responsible for this case (Chang et al 2019;Shi et al, 2020).…”
Section: Refined Manco Scalementioning
confidence: 99%
“…With the increasing global demand for oil and natural gas resources, unconventional oil and gas resources, such as volcanic gas reservoirs, have become a new field for global oil and gas exploration and development (Stagpoole et al, 2001;Polyansky et al, 2003;Feng et al, 2006;Wu et al, 2006;Shi B. et al, 2020). China has become the main subject for the global volcanic rock oil and gas reservoir exploration practice and has made major breakthroughs in the exploration of volcanic rocks in the Songliao basin, Sichuan basin, and Junggar basin (Feng et al, 2008;Feng et al, 2014;Gao, 2019;Li, 2022;Mao et al, 2015;Chang et al, 2019;Wen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%